ID 396 – On the relationship between inter saccadic interval and object velocity in a reaching movement task. Issue 3 (March 2016) - Banea, O.C.; Casanova-Molla, J.; Morales, M.; Cabib, C.; Arca, R.; Brum, M.; Valls-Solé, J.
Abstract : Objective: We aimed to investigate hand movement onset (HMO), saccadic reaction time (SRT) and the interval between the initial saccade and the corrective saccade (ISI) during a reaching movement task. Methods: Seven subjects, aged 29–39, participated in the study. We projected a scene of a penalty striker-goalkeeper combination and we asked participants to stop the ball (target) by using a linear joystick with the dominant hand. Two series of 20 trials at target velocities of 700 and 1400 pixels/s were performed. The eye-movement angle was 20° from initial fixation point. We measured eye saccade duration (SD) and peak velocity (PV), HMO latency, SRT and ISI in trials in which the subject stopped the ball. Results: At low velocity, there were a similar amount of trials in which the hand was activated before and those in which it was activated after the eyes. At high target velocity, SRT and HMO had shorter time difference between them, PV was increased and ISI had a shorter duration while SD didn't change. Conclusions: The evaluation of the ISI is of interest for the assessment of increased qualitative workload. Motor hand preparation seems to occur concomitantly and sometimes before any afferent feedback from eye-saccade signals in eye-hand movement tasks.